Altruistic Behavior of Students in SMA N 1 Kampung Dalam Padang Pariaman Regency and The Implication in Guidance and Counseling - Ulfa Sari Neli; Indah Sukmawati (Universitas Negeri Padang, 2019)
This research is motivated by the phenomenon of students who lack empathy to help friends who need help. Altruistic behavior is an action taken by someone to provide assistance to others voluntarily and sincerely without expecting anything in return. This research aims to describe the altruistic behavior of students in terms of: (1) sharing, (2) cooperating, (3) helping, (4) contributing, (5) honesty, (6) generosity, and (7) consider the rights and welfare of others. This research uses quantitative methods with descriptive type. The population of this study were 601 high school students in Kampung Dalam Padang Pariaman Regency. The total sample of 240 people was selected using the Simple Random Sampling technique. The research instrument used was an altruistic behavior questionnaire for students. Data were processed using descriptive statistical analysis techniques. The results of the study revealed the altruistic behavior of students on; (1) the sharing aspect is in the medium category, (2) the cooperating aspect is in the high category, (3) the helping aspect is in the high category, (4) the donating aspect is in the category very high, (5) the honesty aspect is in the high category, (6) the generosity aspect is in the high category, (7) the aspect of considering the rights and welfare of others is in the high category. Based on the research findings, it is suggested to the Guidance and Counseling Teachers to be able to provide services in the form of information services, content mastery services, and group guidance services in order to further enhance altruistic behavior in students.